N-acetyl-2-hydroxy-N'-[methoxy(1-methylindol-2-yl)methyl]benzohydrazide - Ariffin, Azhar; Ng, S.W.; Yehye, W.A.; Rahman, N.A. (International Union of Crystallography, 2009)
In the crystal structure of the title Schiff-base, C(20)H(21)N(3)O(4), the amino group forms an N-H center dot center dot center dot O hydrogen bond to the acetyl group of an adjacent molecule, forming a zigzag chain. The 2-hydroxy group is internally hydrogen bonded to the amido group though an O-H center dot center dot center dot O hydrogen bond.